PERAN DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI DAERAH ISTIMEWA YOGYAKARTA DALAM MENGURANGI TINGKAT PENGANGGURAN DI DERAH ISTIMEWA YOGYAKARTA - Tri Lestari; Hanantyo Sri Nugroho (Governance, 2024)
Indonesia has large human resources but the capacity for job opportunities exceeds this, causing unemployment problems. Unemployment is not only a problem for the central government but also for regional governments, as is the case in D.I Yogyakarta. The Manpower Service (Disnaker) has a role in overcoming employment problems which include job opportunities, human resources, worker education, access to training, wages, job protection, by establishing programs to reduce unemployment. To determine the role of the Manpower Office in reducing the unemployment rate in D.I Yogyakarta, researchers conducted research using a descriptive approach using observation, interviews and documentation methods in collecting data. Based on research, the Manpower Office uses priority programs, namely the Workforce Placement program, Job Opportunity Expansion Program and Job Training Program. In this case, the Manpower Office plays a role in reducing the number of unemployed in D.I Yogyakarta in 2022.